2020
DOI: 10.1136/svn-2019-000303
|View full text |Cite
|
Sign up to set email alerts
|

Advances in endovascular aneurysm management: coiling and adjunctive devices

Abstract: Endovascular coil embolisation continues to evolve and remains a valid modality in managing ruptured and unruptured cerebral aneurysms. Technological advances in coil properties, adjunctive devices and interventional techniques continue to improve long-term aneurysm occlusion rates. This review elaborates on the latest advances in next-generation endovascular coils and adjunctive coiling techniques for treating cerebral aneurysms.on June 9, 2020 by guest. Protected by copyright.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…The development of aneurysm clips and effective microsurgical techniques (163,164), pioneered in 1911 by Harvey Cushing's invention of the silver clip (165), significantly improved aneurysmal rebleeding rates. More recently, endovascular coiling has emerged as a less invasive alternative to surgical clipping: the aneurysm is accessed with a microcatheter and platinum coils are deployed into the aneurysm, stimulating the formation of a clot that permanently occludes the aneurysm (166,167). Although re-bleeding remains a significant risk for SAH patients (11), cerebrovascular constriction and ischemia has now become the primary cause of death and disability in SAH patients who survive the initial rupture (1,11,12).…”
Section: Clinical Interventions For Ischemia In Sahmentioning
confidence: 99%
“…The development of aneurysm clips and effective microsurgical techniques (163,164), pioneered in 1911 by Harvey Cushing's invention of the silver clip (165), significantly improved aneurysmal rebleeding rates. More recently, endovascular coiling has emerged as a less invasive alternative to surgical clipping: the aneurysm is accessed with a microcatheter and platinum coils are deployed into the aneurysm, stimulating the formation of a clot that permanently occludes the aneurysm (166,167). Although re-bleeding remains a significant risk for SAH patients (11), cerebrovascular constriction and ischemia has now become the primary cause of death and disability in SAH patients who survive the initial rupture (1,11,12).…”
Section: Clinical Interventions For Ischemia In Sahmentioning
confidence: 99%
“…Flow diverter devices may be a feasible option in these cases. 7,8,12,17,18,22,23 In the current study, adjunctive balloon angioplasty was employed in 5 (5.2%) patients, while coiling of the aneurysmal sac was carried out in 12 (12.5%). Angioplasty was employed in 1 patient with an anterior cerebral artery dissecting aneurysm in whom the device had landed on the terminal internal carotid artery causing flow-limitation in the middle cerebral artery, which was described above.…”
Section: Discussionmentioning
confidence: 94%
“…4,5 Flow diverter devices thus expanded the interventionists' armamentarium and were found to be a safe and effective treatment; unlike coiling, the occlusion rates were better the longer the follow-up. 6,7 Though they are especially useful for unruptured aneurysms, they may also be of use for some ruptured subtypes, like blister-like aneurysms, in which they may be the mainstay therapy. 8 The treatment of aneurysms with characteristics such as complex morphology, fusiform, blister-like, wide neck, or large size has been revolutionized with the introduction of flow diverter stents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies and multicenter trials with long-term follow-up reported an aneurysm occlusion rate of 90–96% ( 28 30 ). In the present study, the 6-month follow-up DSA after coil treatment showed an aneurysm occlusion rate of up to 94.66% (i.e., RROC class I and class II) for patients assigned to the Avenir group and 96.95% for those in the Axium group.…”
Section: Discussionmentioning
confidence: 99%